2016
DOI: 10.3389/fnagi.2016.00084
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve in Dementia: Implications for Cognitive Training

Abstract: Cognitive reserve (CR) is a potential mechanism to cope with brain damage. The aim of this study was to evaluate the effect of CR on a cognitive training (CT) in a group of patients with dementia. Eighty six participants with mild to moderate dementia were identified by their level of CR quantified by the CR Index questionnaire (CRIq) and underwent a cycle of CT. A global measure of cognition mini mental state examination (MMSE) was obtained before (T0) and after (T1) the training. Multiple linear regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 54 publications
2
77
2
2
Order By: Relevance
“…Woods et al 2012;van Nes, 2013;Genoe & Dupuis, 2014;Hill et al 2017;Mondini et al 2016;Spector et al, 2017 Individual activities Individual activities as a source to gain strength and to nurture social relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Woods et al 2012;van Nes, 2013;Genoe & Dupuis, 2014;Hill et al 2017;Mondini et al 2016;Spector et al, 2017 Individual activities Individual activities as a source to gain strength and to nurture social relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, with regards to the Stroop test, we used the Interference index proposed by Chafetz and Matthews (2004) . In order to test the role of different predictors regarding CT outcomes in the language domain we have followed a procedure described in Mondini et al (2016) . The measures employed in the analyses resulted from subtracting the baseline scores to the endpoint scores in each of the selected dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…For example, lifestyle factors, occupation attainment or education (cognitive reserve proxies) influence individuals’ cognition along life ( Stern, 2012 ). In this vein, Mondini et al (2016) have shown that cognitive reserve (CR) can modulate the general cognitive status (measured by Mini-Mental State Examination; MMSE onward) after a CT program and should be considered as a predictor of CT efficacy in older adults with mild to moderate dementia. In Spain a recently published study ( Lojo-Seoane et al, 2018 ) have shown the influence of CR on episodic memory, WM, and general cognitive performance in adults with subjective cognitive complaints evaluated at baseline and at a follow-up after an interval of about 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating data come from postmortem brain analyses, reporting individuals with high amounts of both A␤ and neurofibrillary tangles who failed to show overt behavioral changes during life [80]; 2) CR can be assumed to exert both global and regional-specific effects in terms of neural reserve and neural compensation. Those underlying substrates vary depending on the pathology and interact with both gray and white matter such as that, in the healthy controls, differences between individuals with high and low CR can be observed along those regions that are generally most affected with normal aging, whereas the same difference will be noticeable in the MCI/AD patients mostly along those regions involved in the pathological degeneration; 3) Despite high CR acting in ensuring better cognitive performances in the face of the same underlying degree of pathology, once diagnosed, those same patients tend to progress faster and to benefit less from interventional therapies (as evidenced by few studies comparing the cognitive benefits of AD patients with high or low CR following extensive cognitive and motor trainings [24,25]).…”
Section: Associations Between Structural Measures and Cr In Healthymentioning
confidence: 99%
“…Within the aging population, the role of CR becomes even more important when considered in the clinical frame, given that several studies have reported CR as involved in exerting a protective role in the face of neurodegenerative pathologies [13][14][15], delaying their clinical worsening [3,16], and in ensuring better cognitive performances [17]. However, once clinically reaching the time of AD diagnosis, individuals with higher CR have also been reported to progress faster within the disease [18][19][20][21][22][23] and to benefit less from interventional therapies [24,25]. On the other hand, within the healthy population, CR has been generally associated with longer rates of survival [11] and an overall better quality of life [26].…”
Section: Introductionmentioning
confidence: 99%